One man and his log: Charles Elton’s pioneering studies of dead wood at Wytham Woods - Kirby, K (Royal Forestry Society, 2017)
The importance of dead wood for biodiversity is now widely accepted but forty years ago this was far from the case. However a valuable reference point then was Charles Elton’s chapter on dead wood in The Pattern of Animal Communities (1966) which states in the first sentence that ‘dying and dead wood provides one of the two or three greatest resources for animal species in a natural forest’. Recently Charles Elton’s diaries have been digitised (Elton, 1942-1965), detailing accounts of about 400 visits to Wytham Woods. They can be used to explore the development of his interest in dead wood.